Sources of financial assistance for households suffering an adult death in Kagera, Tanzania - Lundberg, Mattias K. A. 1996- (Policy research working paper, 2000)
Why do some households manage better than others in overcoming the impact of an adult death? The household's ability to cope is a function of the resources it can command, including its access to private networks for social insurance and credit. Public intervention can reduce vulnerability ex ante, or target assistance ex post, to the hardest-hit households